Kebangkitan Trend Aplikasi Media Sosial TikTok dalam Perspektif Hukum Islam - Helandri, Joni; Setiawan, Alpat Reza; Putra, Trio; Prabu, Rama; Jaya, Abdillah (Hutanasyah : Jurnal Hukum Tata Negara, 2023)
The social media application TikTok has become a global phenomenon that influences people's social and cultural life. In the context of Islamic law, TikTok's rapid growth raises questions about the app's suitability and compliance with Islamic legal principles. In this journal, we analyze the rise of the TikTok trend from the perspective of Islamic law. Through a qualitative research approach, we investigate the positive and negative impacts of TikTok as well as the implications of Islamic law for its use. We found that TikTok offers benefits in the form of creativity, entertainment and business opportunities, but it can also involve content that is inconsistent with Islamic values. Based on these findings, we recommend the application of criteria and restrictions on the use of TikTok in accordance with Islamic law, as well as the need for public education and awareness regarding the implications of Islamic law in the context of social media. Governments and legal institutions also need to play an active role in regulating and overseeing the use of TikTok.